Potential alternative and novel biomarkers for paediatric MAFLD: exploratory evidence from a Chinese cohort - Fan Yang; Mengyuan Hu; Lulian Xu; Xiaowei Zheng; Lihong Zhu; Le Zhang; Haoyang Zhang (BMC Gastroenterology)
Abstract Background While the associations between pediatric non-obese metabolic dysfunction-associated fatty liver disease (MAFLD) and multiple diagnostic biomarkers are well-established, the role of a broader range of blood-based, urine-based, and body composition-based biomarkers for monitoring MAFLD are needed. Methods A pediatric cohort was established in Wuxi, China. We measured body composition biomarkers, blood-based and urine-based biomarkers, and liver stiffness in participants to diagnose MAFLD and identify alternative and novel potential biomarkers for MAFLD. Body mass index (BMI), high-density lipoprotein cholesterol (HDLC), triglycerides, glucose, systolic blood pressure (SBP), diastolic blood pressure (DBP), and waist perimeter were used as MAFLD diagnostic biomarkers. To identify alternative biomarkers, we performed correlation analysis to determine biomarkers exhibited strong correlation (|r| > 0.8, p-value < 0.05) with diagnostic biomarkers. To identify novel potential biomarkers, we performed regression analysis to determine biomarkers associated with MAFLD (p-value < 0.05 in stepwise multivariate regression) among the remaining biomarkers that are not related to the diagnostic biomarkers. Results Out of 1,108 participants who completed all examinations (N biomarker = 91), 113 participants were diagnosed with MAFLD (prevalence: 14.99% in boys and 5.18% in girls). 27 biomarkers that were strongly correlated with diagnostic biomarkers were identified as alternative biomarkers. A multivariate logistic regression analysis identified 9 novel potential biomarkers including 5 blood-based biomarkers (plateletocrit, calcium, insulin, AST/ALT ratio, total bilirubin), urine pH, and body fat measurements in the arm, leg, and thigh. Conclusions This study illustrated the characteristics and potential alternative and novel biomarkers of MAFLD based on a Chinese paediatric cohort. These findings posed new paths in guiding the prevention and early diagnosis and prevention. Trial registration This trial was registered in the Chinese Clinical Trials Registry (ChiCTR2400080508). The date of first registration, 01/31/2024. Retrospectively registered.